Dielectric spectroscopy of CuInSe₂ single crystals - Mustafaeva, S.N.; Asadov, S.M.; Guseinov, D.T.; Kasimoglu, I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The results of high-frequency dielectric measurements with obtained α-CuInSe₂ single crystals provided an opportunity to determine the mechanisms of dielectric losses and charge transport, and also to evaluate the density of states at the Fermi level; the average time of charge carrier hopping between localized states, average hopping distance, scattering of trap states near the Fermi level; concentration of deep traps responsible for hopping conductivity in alternate electric fields.